Architectural acoustics illustrated - Ermann, Michael (Michael A.) (Wiley, 2015)
"Translates the quantitative and qualitative content of acoustics into the graphic language of architecture and outlines the best practices for limiting or mitigating noise in buildings"--Provided by publisher.